2006
DOI: 10.1007/s11064-006-9220-x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Severity of Experimental Autoimmune Encephalomyelitis in GMF-Deficient Mice

Abstract: Glia maturation factor (GMF), a highly conserved brain-specific protein, isolated, sequenced and cloned in our laboratory. Overexpression of GMF in astrocytes induces the production and secretion of granulocyte-macrophage-colony stimulating factor (GM-CSF), and subsequent immune activation of microglia, expression of several proinflammatory genes including major histocompatibility complex proteins, IL-1beta, and MIP-1beta, all associated with the development of experimental autoimmune encephalomyelitis (EAE), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 41 publications
5
51
0
Order By: Relevance
“…We reported that the overexpression of GMF in astrocytes leads to the destruction of primary oligodendrocytes, the myelin-forming cells in the central nervous system, by interactions between astrocytes, microglia, and oligodendrocytes. These results suggested a novel pathway of GMF initiated cytotoxicity of brain cells, and implicated its involvement in the pathogenesis of inflammatory demyelinating diseases of the central nervous system such as multiple sclerosis/ experimental autoimmune encephalomyelitis (Menon et al, 2007;Zaheer et al, 2007a;Zaheer et al, 2007b;Zaheer et al, 2007c;Zaheer et al, 2007d). In the present report we show that the overexpression of GMF in neuroblastoma N18 cells directly induces caspase-dependent apoptosis mediated by GSK-3β activation.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…We reported that the overexpression of GMF in astrocytes leads to the destruction of primary oligodendrocytes, the myelin-forming cells in the central nervous system, by interactions between astrocytes, microglia, and oligodendrocytes. These results suggested a novel pathway of GMF initiated cytotoxicity of brain cells, and implicated its involvement in the pathogenesis of inflammatory demyelinating diseases of the central nervous system such as multiple sclerosis/ experimental autoimmune encephalomyelitis (Menon et al, 2007;Zaheer et al, 2007a;Zaheer et al, 2007b;Zaheer et al, 2007c;Zaheer et al, 2007d). In the present report we show that the overexpression of GMF in neuroblastoma N18 cells directly induces caspase-dependent apoptosis mediated by GSK-3β activation.…”
Section: Introductionsupporting
confidence: 65%
“…The results also demonstrate that the increased release of GMF-dependent microglial proinflammatory cytokines is cytotoxic to oligodendrocytes, the myelin-forming cells of the central nervous system (Zaheer et al, 2007b). We described novel interactions of brain cells to produce the mediators of neurodegenerative diseases such as multiple sclerosis (MS) and experimental autoimmune encephalomyelitis (EAE) (Zaheer et al, 2007a;Zaheer et al, 2007b;Zaheer et al, 2007c).…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies on glia maturation factor (GMF), a brain-specific protein, isolated, sequenced and cloned in our laboratory (Kaplan et al, 1991;Lim et al, 1989;Lim et al, 1990), have given new insights into its role in immunomodulatory and proinflammatory functions in CNS (Lim and Zaheer, 1996;Lim et al, 2000;Zaheer et al, 2002;Zaheer et al, 2004;Zaheer et al, 2006;Zaheer et al, 2007). We have established that overexpression of GMF in astrocytes leads to immune activation of microglia, through secretion of granulocyte-macrophage-colony stimulating factor (GM-CSF), and resulting in production of several pro inflammatory mediators that destroy oligodendrocytes, the myelin forming cells in CNS.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that intracellular GMF is involved in the pathogenesis of inflammatory diseases of the central nervous system such as MS and EAE. More recently, we have shown that GMF −/− mice (GMF-KO) were resistant to EAE induced by active immunization with MOG-35-55 antigen, whereas GMF +\+ (Wt) mice developed the disease characterized by significantly increased inflammation and demyelination in the central nervous system (Zaheer et al, 2007). In the present study, to analyze the inflammatory and immune mechanisms underlying the beneficiary effects of GMF deficiency in mice, we compared the development of EAE in wild type (Wt) and GMF-KO mice in both active and adoptive transfer models.…”
Section: Introductionmentioning
confidence: 99%
“…gMFβ is an intracellular protein that is primarily localized in the mammalian central nervous system and plays an important role in regulating the growth and development of glial cells and neurons. gMF is found to mediate apoptosis in glioblastoma cells as well as the development of inflammation (28)(29)(30). studies have suggested that gMF interacts with ADF/ cofilin to promote the remodeling and/or disassembly of brain cortical actin structures (31).…”
Section: Discussionmentioning
confidence: 99%